SWATLitho: A hydrogeochemical model to estimate daily geochemical loads at the catchment scale. (January 2021) - Lechuga-Crespo, Juan Luis; Sauvage, Sabine; Ruiz-Romera, Estilita; George, Chris; Sánchez-Pérez, José Miguel
Abstract: The increase in water salinisation in catchments has led to increased concern in assessing major ion loadings in freshwater environments. In this study, we couple a globally fitted model on chemical weathering to the Soil and Water Assessment Tool (SWAT) for the estimation of daily geochemical loadings at the catchment scale, "SWATLitho". The enhancements include i) a modification on the discretisation of the catchment area by integrating a layer describing lithology (QSWATLitho), and ii) the development of an extra module to compute the ionic loads derived from the chemical weathering of rocks. The model is sensitive to input data resolution, yielding the best results when including local data. Larger spatial and temporal discrepancies are found in one tributary, associated with point sources impacting the loadings; while these discrepancies are lower at headwater subbasins. Results suggest that, despite of these discrepancies, the average simulation of the daily ionic loadings is reasonable. Highlights: A lithological layer coupled to SWAT Hydrological Response Units has been introduced. A simple model has been implemented to assess daily cation and anion fluxes. Daily geochemical loads have been estimated using SWAT water balance.